1995
DOI: 10.1111/j.1365-2559.1995.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein–Barr virus only in lymphoepithelial carcinomas among primary carcinomas of the lung

Abstract: DiscussionNuclear and architectural changes in endometrial glands in pregnancy were recorded by Arias-Stella in 19 542. Epithelial changes of the Arias-Stella phenomenon have also been well recorded at extrauterine sites including the endocervix" Until a recent report, the Arias-Stella phenomenon had been thought to be characterized by either no mitotic activity or only sparse normally formed mitoses'.In their recent paper Arias-Stella et a1.l have shown that mitotic activity and even abnormal mitotic figures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Kasai et al [1994] reported that ®ve cases (6.2%) of 81 lung cancers in northern Japan were associated with EBV and indicated that the morphological features of EBV-associated lung cancers were not restricted to the lymphoepithelioma-like carcinoma. However, Chan et al [1995] detected EBV in seven lymphoepithelioma-like carcinomas, but not in 59 lung carcinomas in Chinese patients with other histological types. In the south part of Kyushu, Japan, none of the 75 lung carcinomas, including two lymphoepitheliomalike tumors, were positive for EBV.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Kasai et al [1994] reported that ®ve cases (6.2%) of 81 lung cancers in northern Japan were associated with EBV and indicated that the morphological features of EBV-associated lung cancers were not restricted to the lymphoepithelioma-like carcinoma. However, Chan et al [1995] detected EBV in seven lymphoepithelioma-like carcinomas, but not in 59 lung carcinomas in Chinese patients with other histological types. In the south part of Kyushu, Japan, none of the 75 lung carcinomas, including two lymphoepitheliomalike tumors, were positive for EBV.…”
Section: Discussionmentioning
confidence: 87%
“…Primary lymphoepithelioma-like carcinoma of the lung was associated often with EBV in Asians but not in Caucasians [Butler et al, 1989;Gal et al, 1991;Pittalug et al, 1993;Higashiyama et al, 1995;Chan et al, 1995 ]. Kasai et al [1994] reported that ®ve cases (6.2%) of 81 lung cancers in northern Japan were associated with EBV and indicated that the morphological features of EBV-associated lung cancers were not restricted to the lymphoepithelioma-like carcinoma.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several other studies performed on a higher number of adenocarcinomas showed no evidence of EBV either in Asian or Caucasian patients [5,6,7,28]. However, EBV has been shown to infect and replicate in some epithelial cells and to be present in broncho-alveolar lavage, suggesting that the lung may be a reservoir of EBV [20,25].…”
Section: Discussionmentioning
confidence: 93%